The impact and outcomes of (non-education) doctorates: the case of an emerging Bhutan - Maxwell, Tom W.; Chophel, Dendup (Higher Education, 2020)
This is a follow-up study of the impact of education doctorate holders in Bhutan (Maxwell 2018). A representative sample of doctorate holders contributed to this qualitative study. There were anticipated personal outcomes of gains in confidence and self-esteem. There were considerable gains in knowledge and research skills, and mentoring was clearly an important outcome. However, respondents were equivocal about leadership. Workplace conditions appeared to be creating dissatisfaction. Bhutan appears to be close to, or beyond, the cusp where brain drain takes over from brain gain. This, coupled with the under-representation of females amongst doctorate graduates, means development is most likely to be slowed down unless attended to. Ideas for further research are identified.
Created from Fastlane, Scopus look-up
Keywords: Bhutan; Brain drain; Developing country; Doctorate impact; Doctorate outcomes